Os impactos da blockchain nas relações econômicas internacionais - Katz, Ígor Santos (2023)
The purpose of this academic thesis is to analyze some aspects of blockchain technology that may represent a second form, less conventional and driven by the internet, of enhancing international economic relations. This is not merely about concisely recording what is already known or currently communicated about the sophisticated data storage mechanism known as distributed databases, which enable information transmission on a public or private organization's network. This analysis is grounded in the growing use of the internet and the need to harmonize international trade for social development. The relationship between regulatory aspects of trade and blockchain is examined, emphasizing the relevance of this technology as an instrument capable of increasing the efficiency and security of international commercial transactions, regulated through standardized clauses. Given that more than half of the world's population uses the internet, which represents a global reality, it is possible that this technology may become widely disseminated. The theoretical framework of the text is the analysis of blockchain technology as a tool for enhancing international economic relations, considering the growing use of the internet and the need for harmonization of international trade for societal development. Incoterms, standardized clauses in international trade contracts, and their relationship with blockchain technology are mentioned. The adoption of blockchain technology in international economic relations is also addressed, seeking to highlight the importance of technology enhancement for economic development. The objective is to present a theoretical analysis methodology concerning blockchain technology, considering it a suitable tool for improving international economic relations. To do this, the advantages and challenges arising from the adoption of blockchain in these relations are discussed, as well as the legal issues that may emerge from its use. The importance of enhancing the aforementioned technology for economic development is emphasized. Thus, the methodology employed in this work consists of a theoretical analysis based on prior research and studies on the topic in question. Divided into 3 chapters, the study aims to provide a thorough analysis of different aspects related to the use of blockchain technology in the business and global context. The first chapter introduces fundamental concepts about blockchain technology, its principles and foundations, the emergence of a new lex mercatoria; the second analyzes the importance of UN/CEFACT in the context of global trade and how blockchain technology can be a relevant tool to enhance its processes and solutions. Finally, the third chapter aims to discuss how startups are adapting to traditional business concepts and how blockchain technology can be an essential tool in this process. In addition, the success case of Incoterms, an international trade tool, is presented, and how the adoption of blockchain technology can face the same challenges that Incoterms faced in becoming effective in international trade. In light of the relentless pursuit of trade facilitation and promoting good faith in international commercial relations, this study is dedicated to the topic with the aim of verifying whether it is possible to confirm the thesis that the enhancement of blockchain technology is fundamental for the strengthening of companies, for the development of Brazil, and especially for international economic relations